Perbandingan beberapa indeks kriteria penentuan jumlah optimal kelompok=Comparison of some criterion indexes for determining the optimal number of clusters - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This article considers the problems of estimating the optimal number of groups. We are interested in the comparison of some criterion indexes for overcome the problems. We have studied the gap statistic to estimate the optimal number of groups. The effectiveness of the gap statistic is compared with many methods that has been proposed for estimating the number of clusters by Calinski-Harabazs, Hartigan, and Krzanowski-Lai. Comparisons based on models with various the number of variables and sample sizes. The technique uses the output of some clustering methods, especially K-Means, and Ward's methods. The result of simulation showed that the gap statistic usually did not distinct with other methods.